Report on the G20 Survey in De-Risking Activities in the Remittance Market - World Bank Group (World Bank, Washington, DC, 2015)
In September 2014, the Group of Twenty (G20) Global Partnership for Financial Inclusion (GPFI) requested the World Bank Group to undertake a survey in the G20 countries on the issue of commercial banks’ actions to de-risk their operations, specifically in relation to non-bank international remittance service providers or, as they are alternatively referred to throughout this report, money transfer operators (MTOs). The objective of the survey was to assess the status of the de-risking phenomenon in the G20 countries, and to collect evidence from which conclusions on the main drivers and the impact for the MTO market could be drawn. The key findings of this survey and the relative recommendations on potential actions are provided in this report to assist the G20 governments, standard setting bodies, private sector entities and the other relevant stakeholders in the financial sector on future discussions on this topic. In addition to working with the G20 on de-risking in the remittance market, the World Bank Group collaborated with the Financial Stability Board (FSB) and the Committee on Payments and Market Infrastructures (CPMI) to conduct a global survey on access to foreign correspondent banking relationships. This survey is focused on banking authorities, large international banks, and regional/local banks. The G20 Finance Ministers and Central Bank Governors endorsed this work in February 2015.